Efficacy of Pegylated Liposomal Doxorubicin in Low-Grade Serous Ovarian Carcinoma. Issue 5 (June 2017) - Rose, Peter G.; Radeva, Milena; Michener, Chad M.; Link, Nicholas; Adbul-Karim, Fadi
Abstract : Objective: The aim of this study was to assess the efficacy of pegylated liposomal doxorubicin (PLD) in low-grade serous ovarian carcinoma (LGSOC). Methods: We retrospectively identified patients with LGSOC who were treated with PLD. Response to therapy was evaluated by RECIST 1.1 criteria. Progression-free survival (PFS) and overall survival were calculated. In addition, PFS on PLD was compared with the patient's most recent PFS on previous therapy. Results: Twenty-four patients were treated with PLD. Three patients were not evaluable, leaving 21 patients evaluable for response. Pegylated liposomal doxorubicin was dosed at 40 mg/M 2 every 28 days except in 7 patients (5 received PLD dosed at 30 mg/M 2 in combination with carboplatin and 2 received PLD dosed at 20 mg/M 2, one of which was in combination with etoposide). Four of the patients who received PLD in combination subsequently received PLD alone for 4+, 12, 21, and 29 cycles, respectively. Three patients (14.3%) had a complete response and remained progression free at 8, 31, and 34 months, respectively. Two of these patients received PLD alone. The third complete response patient initially received PLD in combination with carboplatin and then went on to receive PLD alone during which a complete radiologic response was achieved. No difference in response or PFS by platinum sensitivity was noted ( P s = 0.73 and 0.62, respectively). Fourteen patients had stable disease for a median of 18 months. Among the 14 patients with stable disease, the PFS on PLD exceeded the previous PFS in 11 patients (78.6%) from 1.3 to 20.6 folds, with a median of 3.5 folds. The 2 of the 3 lowest increases in PFSs were seen in patients whose therapy was terminated despite stable disease. Conclusions: Pegylated liposomal doxorubicin is relatively active in LGSOC. The treatment of stable disease resulted in increase in PFS in 78.6% of patients by a mean of 350%.